Memories of exile. Mercedes Fidanza´s artistic-political practices with Sons and Daughters of Exile (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
Between 2002 and 2010 a series of performances and interventions were developed in public space. These practices were developed by Mercedes Fidanza and by the collective Sons and daughters of exile. These actions addressed the political exiles during the last dictatorship since the children's perspective and configured ephemeral territories of memories in different places in Argentina. In this article, we will address these proposals as artistic-political practices in which bodies and objects fold and unfold knowledge and memories of childhoods in dictatorship and whose force of action and intervention lies in social ties as power.